Analisis Pengaruh Strategi Promosi dan Brand Equity Terhadap Keputusan Pembelian Skincare Pada PT Kosmetika Cantik Indonesia - Maulida, Melvi; Rakhmat; Yesi, Reni (Journal of Entrepreneurship and Financial Technology, 2024)
This study aims to determine whether the variables of promotion strategy and brand equity have a significant effect on purchasing decisions on MS Glow skincare. This type of research uses quantitative methods, the sample in this study amounted to 171 respondents. From the results of the study, it shows that partially the promotion strategy and brand equity have a positive effect on purchasing decisions, it can be seen from the results of the multiple regression coefficient analysis Y = 3.549 + 0.7407 (X1) + 0.1828 (X2), which means that if the promotion strategy and brand equity (X1 and X2 = 0) then the purchase decision is 3.549 and if the promotion strategy and brand equity (X1 and X2 = 1) the purchase decision is 0.7407 for X1 and 0.1828 for X2. Based on the calculation of the coefficient of determination analysis R^2 of the eviews program is 0.8446, the correlation analysis of determination R^2 is obtained with a value of Kd = 0.8446, which means that the contribution of promotional strategies and brand equity can explain purchasing decisions by 84.46%. And the remaining 15.54% is influenced by other variables not examined in this study.